2006
DOI: 10.1016/j.jsv.2005.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The second spectrum of Timoshenko beam theory—Further assessment

Abstract: A review of contributions and views on the second spectrum of Timoshenko beam theory (TBT) over the past two decades, together with some new results, are presented. It is shown that the Timoshenko frequency equation factorises not solely for hinged-hinged end conditions, as is often claimed, but also for guided-guided and guided-hinged; these new cases may be regarded as portions of a multi-span hinged-hinged beam. A higher-derivative Lagrangian that leads directly to the well-known fourth-order Timoshenko bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…Similarly in Ref. [2], for the thin rectangular cross-section, the TBT2 prediction did not provide consistent agreement with any single mode of vibration; at long wavelength it was very close to the second exact asymmetric mode (as one would wish), but as wavelength shortens it became closer to the second symmetric (extensional) mode, then the third asymmetric mode. In both studies it was concluded that the second spectrum predictions of Timoshenko beam theory should be disregarded.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Similarly in Ref. [2], for the thin rectangular cross-section, the TBT2 prediction did not provide consistent agreement with any single mode of vibration; at long wavelength it was very close to the second exact asymmetric mode (as one would wish), but as wavelength shortens it became closer to the second symmetric (extensional) mode, then the third asymmetric mode. In both studies it was concluded that the second spectrum predictions of Timoshenko beam theory should be disregarded.…”
Section: Introductionmentioning
confidence: 61%
“…This allows one to think in terms of a first and second spectrum of natural frequencies, or first and second branches of a wave propagation dispersion diagram. It has been shown recently [2] that the transcendental frequency equation also factorises for guided-guided and guided-hinged conditions; these new end combinations can be regarded as portions of a multi-span hinged-hinged beam. Below the second spectrum cut-off frequency given by o co ¼ ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi kAG=rI p , TBT predicts both propagating (TBT1) waves, and evanescent (TBT2) waves associated with the hyperbolic spatial functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the relatively poor accuracy of the second spectrum with respect to detailed theories cannot be a measure of its physical meaningfulness (contrary to the suggestion of Stephen (2006) and Stephen & Puchegger (2006)). …”
Section: ã2mentioning
confidence: 80%
“…Levinson & Cook (1982), Stephen (1982) and Nesterenko (1993) did realize the mathematical existence of these roots (clues coming from the quadratic equation (2.5)) but were unsure of their physical meaning. Since (i) the first root in equation (2.7) can be obtained by incorrectly treating the problem as one of regular perturbation while the second root cannot be, (ii) the second spectrum is less accurate with respect to three-dimensional theories, (iii) the so-called Ostrogradsky energy is negative (Nesterenko 1993), and (iv) only those frequencies 'which turn into frequencies of the EB equation' should be regarded as physical (Nesterenko 1993) when e and s approach zero, the second spectrum has been rejected (Levinson & Cook 1982;Stephen 1982Stephen , 2006Chervyakov & Nesterenko 1993;Nesterenko 1993;Stephen & Puchegger 2006) as being non-physical and a mathematical artefact of the correction to the EB field equation. There are several fallacies in these objections which will be discussed in the following.…”
Section: The Physical Meaningfulness Of the Second Spectrum And The Ementioning
confidence: 99%